ANALISIS TINDAK TUTUR DIREKTIF DALAM FILM NANTI KITA CERITA TENTANG HARI INI KARYA ANGGA DWIMAS SASONGKO - Berlianda, Cansa; Dr. Gunta Wirawan, M.Pd.; Dr. Safrihady, S.Pd., M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the form and function of the directive speech acts contained in the film we will tell you about today the work of Angga Dwimas Sasongko. The data source of this research is the dialogue of all characters in the film. Research uses descriptive qualitative methods with a pragmatic approach. Data was collected through a refer and record technique, then analyzed by referring to the theory of directive speech acts put forward by Searle. The results showed that in the film later we told about today as many as 66 directive speech action data which is divided into 6 types of directive speech acts.